One team, one space, one Caribbean - Mottley, Mia Amor...[et al.] (IMPACS Port of SpainTT, 2007)
Documents in a series of reports, the elements of the regional security strategy for Cricket World Cup 2007, the plans derived therefrom, the institutional framework established for their implementation, the challenges, successes and, most importantly the legacy.